ANALYSIS OF FACTORS INHIBITING THE IMPLEMENTATION OF K3 IN CONSTRUCTION PROJECTS - Ariyanti, Menik; Wateno Oetomo; Sajiyo, Sajiyo (International Journal Science and Technology, 2024)
Low implementation of K3 in construction projects can cause the safety and health of construction workers to be given less attention, so that construction workers feel less safe and comfortable, which can result in a decrease in performance levels. The impact of non-optimal performance results in the project being carried out not being able to meet the quality requirements that have been set. Based on data analysis from observations on the Kapas-Glendeng 8 bridge widening construction project, Bojonegoro Regency, there are inhibiting factors in implementing the occupational health and safety management system, namely workforce competency, work experience in the construction sector, job training, ability to access information via digital media. , worker involvement in making regulations, understanding and awareness in wearing PPE, reporting procedures, data recording and documentation.